Low dietary diversity is associated with stunting among children aged 8-23 months in stunting locus area, Yogyakarta, Indonesia - Lestari, Putri; Irawati, Winda; Hositanisita, Hastrin; Paratmanitya, Yhona; Nurhayati, Eka; Yi, Lee Yi; Ariftiyana, Siska; Rahayu, Herwinda Kusuma (Alma Ata University Press, 2024)
Background: Stunting is impaired growth and development that children experience, caused by poor nutrition during 1000 days of life. Dietary diversity is one of the core indicators for assessing diet quality and adequacy of complementary feeding.Objectives: This study aimed to analyzed the relationship between dietary diversity and stunting among children aged 8-23 months in Pajangan District, Bantul Regency, Yogyakarta.Methods: This was a quantitative observational cross-sectional study. Purposive random sampling was used to recruit a total of 167 children aged 8-23 months with their mothers/ caregivers as respondents. Individual dietary diversity was assessed by minimum dietary diversity with the consumption of 5 or more food groups of the total 7 food groups. Logistic regression, chi-square test, and descriptive statistics were used for data analysis.Results: Results showed that prevalence of stunting was 32.3% and 54.5% of children did not meet the minimum dietary diversity. There was a significant relationship between dietary diversity on complementary feeding and stunting (p=0.005, OR=2.558; 95%CI= 1.422-4.142). Furthermore, other factors related to dietary diversity were child’s age, mother's employment status, father's education, father’s employment, and family income.Conclusions: There was a relationship between dietary diversity and stunting among children aged 8-23 months in Pajangan District, Bantul Regency, Yogyakarta. Strategy to improve dietary diversity on complementary feeding are needed to prevent child malnutrition. KEYWORDS: complementary feeding; dietary diversity; stunting